2006
DOI: 10.2298/gensr0603251i
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among alfalfa yield components

Abstract: Presented in this paper are the results of our study of correlations among yield components in ten alfalfa genotypes under open pollination (polycross) conditions. The study was conducted between 2000 and 2002 at the Rimski Sancevi Experiment Field of the Institute of Field and Vegetable Crops in Novi Sad. Highly significant correlations were found between pod number per inflorescence and seed number per inflorescence (r= 0.645) as well as between seed number per pod and seed number per inflorescence (r= 0.685… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…The reported values of 33.16, 20.10 and 16.08% for factors year (Y), genotype (G) and genotype x year (G x Y) interaction, respectively, revealed their significant impact on the degree of phenotypic expression of seed yield (Table 5). Ilic and Dukic (2006) found that the degree of penotypic expression of seed yield is highly influenced by year, as well as by genotype x year interaction when investigated 10 genetically divergent genotypes. А significant influence of the year and the genotype on seed weight per plant was also reported by Lakić et al (2022) but the authors argued that the genotype x year interaction had no significant effect on the trait.…”
Section: Resultsmentioning
confidence: 99%
“…The reported values of 33.16, 20.10 and 16.08% for factors year (Y), genotype (G) and genotype x year (G x Y) interaction, respectively, revealed their significant impact on the degree of phenotypic expression of seed yield (Table 5). Ilic and Dukic (2006) found that the degree of penotypic expression of seed yield is highly influenced by year, as well as by genotype x year interaction when investigated 10 genetically divergent genotypes. А significant influence of the year and the genotype on seed weight per plant was also reported by Lakić et al (2022) but the authors argued that the genotype x year interaction had no significant effect on the trait.…”
Section: Resultsmentioning
confidence: 99%
“…These findings agreed with the result of this experiment. Ilić and Đukić (2006) found that the correlation between seeds per pod and seed yield was not meaningful.…”
Section: Discussionmentioning
confidence: 97%
“…Alfalfa seed yield was reported to be significantly correlated with yield components (Ilić and Đukić, 2006). Bodzon (2004) reported that flowers per raceme had a significant relation with seed yield.…”
Section: Discussionmentioning
confidence: 99%
“…Bu durum, özellikle bitkilerin aktif olarak geliştiği Nisan, Mayıs ve Haziran ayları içerisinde düşen yağış miktarının yıllara göre önemli derecede farklılık göstermesi nede niyle bitkilerde tohum oluşturan sap sayısının farklılık göstermesi ile açıklanabilir. Zira bu konuda yapılan bir çok çalışmada salkımda çiçek, meyvede tohum sayısı ve tohum verimlerinin çeşitlere ve yıllara göre önemli dere cede değiştiği saptanmıştır 18,19,21 . Araştırmanın yürütül düğü üç yılda da kafes dışı koşullarda bitki başına tohum verimi kafes içi koşullardakine göre istatistiksel olarak önemli derecede daha yüksek olmuş ve üç yıllık ortala maya göre kafes dışı koşullarda 12.7 g olan bitki başına tohum verimi, kafes içi koşullarda 0.8 g olmuştur.…”
Section: Bitki Tohum Verimi (Gr/bitki)unclassified